Cardiac resynchronization therapy reduces expression of inflammation-promoting genes related to interleukin-1β in heart failure. Issue 7 (15th October 2019) - Bilchick, Kenneth; Kothari, Hema; Narayan, Aditya; Garmey, James; Omar, Abdullah; Capaldo, Brian; McNamara, Coleen
Abstract: Aims: In light of recent data regarding inflammatory signalling pathways in cardiovascular disease and the recently demonstrated impact of pharmacologic inhibition of interleukin-1β (IL-1β) in heart failure, the primary aim was to assess the physiologic effects of cardiac resynchronization therapy (CRT) on the expression of systemic inflammatory, immune-modulatory, metabolic, and apoptotic genes in peripheral blood mononuclear cells (PBMCs) of patients with heart failure. Methods and results: We used RNA sequencing (RNA-Seq) and reverse transcription quantitative real-time polymerase chain reaction (RT-qPCR) to identify gene expression changes in PBMCs in response to CRT. In total, 27 patients were analysed: 12 with heart failure undergoing CRT, 6 with heart failure undergoing standard implanted cardioverter defibrillators, and 9 with coronary artery disease but not heart failure. In CRT patients (median age 65.5 years, interquartile range 63.0–66.8 years, 33% female), RNA-Seq analysis identified 40 genes, including multiple genes associated with the IL-1β pathway, with significant correlations (false discovery rate < 0.05) with four key CRT response measures. CRT was associated with suppression of PBMC expression of IL-1β (1.80-fold decrease, P  = 0.047), FOS proto-oncogene (FOS) (3.25-fold decrease, P  = 0.01), dual specificity phosphatase 1 (DUSP1) (2.05-fold decrease, P  = 0.001), and early growth response 1 (EGR1) (7.38-fold decrease, P  = 0.03), and suppression was greater in responders vs. non-responders ( P  = 0.03 for IL-1β, P  = 0.02 for FOS, P  = 0.02 for DUSP1, and P  = 0.11 for EGR1). Baseline FOS and DUSP-1 levels were greater in responders vs. non-responders (6.15-fold higher, FOS, P  = 0.002; 2.60-fold higher, DUSP1, P  = 0.0001). CRT responders but not non-responders showed higher baseline gene expression of FOS ( P  = 0.04) and DUSP1 ( P  = 0.06) compared with control patients without heart failure. Baseline serum high-sensitivity C-reactive protein levels were 3.47-fold higher in CRT responders vs. non-responders ( P  = 0.008). Conclusion: Treatment of heart failure with CRT resulted in decreased PBMC expression of genes linked to inflammation. Moreover, CRT responders had higher expression of these inflammatory genes prior to CRT and greater suppression of these genes after CRT compared with non-responders. Graphical Abstract: